WÂQI’ TA’LÎM MAHÂRAH AL-KITÂBAH BI INDÛNÎSIYYÂ MUSYKILATAN WA HULÛLAN - Ahmad Muradi (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2018)
The purpose of this study was to describe the variant of student thesis on learning to write Arabic language and description of the students’ thesis results. This research used descriptive qualitative research method by using content analysis. The author analyzed 42 related theses of writing Arabic in accordance with the variant of kitâbah discussion and the results of those theses. The results of this study were 1) the study variant of Arabic writing consisted of 6 studies on Arabic painting, 16 studies on writing imlâ, 19 studies on the making of insyâ, and 1 study on Arabic writing material analysis. 2) The result of this thesis research was that experimental study about the use of technique, method, and media was effective in improving learning result except one research stating ineffective. The results of this research showed that there were alternatives that can solve the problem of learning to write Arabic nowadays.